Antimony - Botnen Smebye, Andreas; Botnen Smebye, Andreas; Braibant, Caroline; Braibant, Caroline; Caplette, Jaime N.; Caplette, Jaime N.; Egodawatta, Lakmini P.; Egodawatta, Lakmini P.; Fabian, Karl; Fabian, Karl; Filella, Montserrat; Filella, Montserrat; et al. (De Gruyter, 2021)
Antimony (Sb) is an exciting chemical element ubiquitously present in our daily lives. This book provides a coherent and interdisciplinary picture of our current understanding of this element. Subjects ranging from its mineralogy, mining and environmental chemistry to its potential impact in ecosystems and human health are discussed in this monograph.